Spatio-temporal dynamics of forest fire occurrence in Yunnan, China from 2001 to 2021 based on MODIS - Hang Deng; Dong Li; Shanshan Cai; Fan Zhao; Junfan Zhao (npj Natural Hazards)
Abstract Under the influence of factors such as climate and land use changes, it is highly useful to investigate the spatio-temporal occurrence characteristics of forest fires using remote sensing data. This study utilized long-term remote sensing data on Active Fire Spots (AFSs), Burned Areas (BA), and Land Cover Types (LCT) in Yunnan Province. Through pixelization of AFSs, spatial extraction, and spatio-temporal clustering, 39,101 Forest Fire Events (FFEs) were identified. The results indicate that FFEs in Yunnan Province exhibit spatio-temporal clustering, with an overall annual fluctuating decline trend. The clustering is more pronounced in spring and winter, with a delayed temporal span. Over 88% of FFEs are concentrated in southern Yunnan, and the frequent occurrence areas have shifted eastward in recent years. This study deepens the understanding of the spatio-temporal dynamics of forest fires and provides a basis for regional forest fire management to promote sustainable development in related fields.